Peran Emotional Intelligence dan Family Dinner Ritual terhadap Life Satisfaction pada Mahasiswa Tahun Pertama - Leonora Jeanifer; Stefani Virlia (Fakultas Psikologi Universitas Pancasila, 2020)
Life satisfaction is an aspect that needs to be considered in individuals, especially in first-year students. First year students undergo a transition period of lectures and belong to the group of emerging adults who are in a phase of instability. Some phenomena related to instability experienced by first-year students and are thought to lead to a decrease in life satisfaction. The purpose of this study is to look at the role of emotional intelligence and family dinner rituals on life satisfaction in first-year students. This research uses a quantitative approach with multiple regression tests. The subjects of this study were 332 first-year active students aged 18-21 years in Surabaya. The results of the study showed a significant influence between emotional intelligence and family dinner ritual on life satisfaction with an effective contribution of 9.1% (R2 = 0.091; p <.05). Family dinner rituals contribute more effectively than emotional intelligence.